STRATEGIES FOR IMPROVING HUMAN RESOURCES THROUGH EDUCATIONAL TOURISM - Mohammad Ali Masyhuri; Sutinem Sutinem; Abdul Mateen (Transpublika Publisher, 2023)
Education is the right of everyone wherever they are, at any age, including economic conditions at any level. The way to obtain knowledge can no longer be limited by anyone and anything nowadays. In this global era, education patterns are increasingly diverse, knowledge transfer activities no longer have to always be carried out in the classroom. The pattern of teaching and learning activities outside the classroom has also been implemented by many educational institutions in many countries, including Indonesia. When teaching and learning activities are carried out outside the classroom, it generally increases interest in learning for students at primary and higher education levels. In this article, we will convey qualitatively the efforts to transfer knowledge outside the classroom in order to increase interest in learning and reduce boredom due to always studying indoors. A two-way interactive atmosphere is one of the effective ways of learning activities to produce better student abilities, in all subjects or certain subjects. The more optimal human resource capabilities are in the future, we can be sure that economic conditions and many other fields will be better and able to compete with other nations.